EFEKTIVITAS TANAMAN NAUNGAN DAN PUPUK BIOPROTEKTAN KOMPOS Trichoderma sp. UNTUK MENGENDALIKAN PENYAKIT BUSUK UMBI PADA TANAMAN BAWANG MERAH - Indiani, Ni Ketut; Lakani, Irwan; Ismail, Rosmini (AGROTEKBIS, 2013)
Onion (Allium ascallonicum L.) is one of horticultural commodities that has high economic value and national priority to cultivate. The purpose of this study was to determine the effectiveness of shade plant and bioprotectant fertilizer (compost + Trichoderma sp.) to control tuber root disease (Fusarium oxysporum) on onion crop. This study used Split plot design, which consists of: (1) shade treatment as the main plot namely: without (A1) and with (A2) shade plants, (2) application of bioprotectant fertilizer (compost + Trichoderma sp.) as the subplot namely: without fertilizer (B0), fertilizer 1 kg/plot (B1), 2 kg/plot (B2), and 3 kg/plot (B3). The results showed that application of shade and fertilizer bioprotectant 3 kg/plot (B3) produced the lowest of tuber rot disease infestation of and the highest levels of onion yield.